2020
DOI: 10.1016/j.cortex.2019.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Anterior temporal lobe is necessary for efficient lateralised processing of spoken word identity

Abstract: In the healthy human brain, the processing of language is strongly lateralised, usually to the left hemisphere, while the processing of complex non-linguistic sounds recruits brain regions bilaterally. Here we asked whether the anterior temporal lobes, strongly implicated in semantic processing, are critical to this special treatment of spoken words. Nine patients with semantic dementia (SD) and fourteen age-matched controls underwent magnetoencephalography and structural MRI. Voxel based morphometry demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…This height threshold was used because a more conservative height threshold of p < 0.05 FWE corrected for multiple comparisons did not yield significant findings. The height threshold used in our study, however, is comparable to those of previous correlational neuroimaging studies on neurodegenerative disease samples of this size (Ghosh et al 2012;Pasquini et al 2015;Cope et al 2020) and remains more stringent than the problematic thresholds of p < 0.01 and p < 0.05 shown to inflate false positive findings in correlative neuroimaging studies relating for example gray matter with genetic variation (Silver et al 2011). An analogous voxel-wise model was used to assess the association between inclusion-bearing VENs and fork cells and white matter atrophy.…”
Section: Experimental Design and Statistical Analysessupporting
confidence: 61%
“…This height threshold was used because a more conservative height threshold of p < 0.05 FWE corrected for multiple comparisons did not yield significant findings. The height threshold used in our study, however, is comparable to those of previous correlational neuroimaging studies on neurodegenerative disease samples of this size (Ghosh et al 2012;Pasquini et al 2015;Cope et al 2020) and remains more stringent than the problematic thresholds of p < 0.01 and p < 0.05 shown to inflate false positive findings in correlative neuroimaging studies relating for example gray matter with genetic variation (Silver et al 2011). An analogous voxel-wise model was used to assess the association between inclusion-bearing VENs and fork cells and white matter atrophy.…”
Section: Experimental Design and Statistical Analysessupporting
confidence: 61%
“…Novel, connectivity-based analysis approaches may help to elucidate mechanisms of pathogenic protein spread: recent work using spectral dynamic causal modelling has suggested that attenuation of inhibitory connectivity in antero-mesial temporal lobes may help drive TDP-43 (type C) pathogenic protein spread in svPPA [62••]. Innovative magnetoencephalography [63][64][65][66] and functional magnetic resonance imaging [29••, 54] paradigms have also shown utility in delineating unique neurophysiological signatures of functional connectivity and plasticity in major PPA variants: these techniques may hold promise as very early markers of neurodegeneration, when atrophy is not prominent [67].…”
Section: The Challenge Of Molecular Diagnosis: Physiological Phenotypmentioning
confidence: 99%
“…People with PPA may benefit from physiologically informed cognitive rehabilitation strategies, akin to strategies designed to enhance neuroplasticity after stroke aphasia [92,93]: recent work suggests that people with all major forms of PPA have retained capacity for perceptual learning of degraded speech [52••], and that patients with nfvPPA show preserved faculty for artificial grammar learning [94], suggesting the need for future trials focused on exposure-based approaches to rehabilitation of agrammatism and degraded speech perception. In svPPA, right-lateralised brain regions show elevated activity in magnetoencephalography when listening to spoken words, whilst dorsal regions appear to compensate for damaged ventral regions when patients read irregular words, together suggesting a degree of functional plasticity in brain networks with relatively preserved integrity [63,64].…”
Section: The Challenge Of Treatment: Optimising Function and Changingmentioning
confidence: 99%
“…Ample evidence for this proposal has been provided by studies on semantic dementia patients, who show specific semantic deficits following impairment of the anterior temporal lobes ( Mion et al., 2010 ; Nestor et al., 2006 ), and fMRI and PET studies demonstrating ATL sensitivity to semantic stimulus and task manipulations ( Crinion et al., 2003 ; Embleton et al., 2006 ; Mummery et al., 2000 ; Rogers et al., 2006 ; Tranel et al., 2005 ; Visser et al., 2012 , 2010 ). Several studies have demonstrated similar effects in brain activity estimated from EEG or MEG data ( Cope et al., 2020 ; Dhond et al., 2007 ; Farahibozorg et al., 2019 ; Marinkovic et al., 2014 , 2003 ; Mollo et al., 2017 ), but the precise time course of semantic processing, as reflected in the brain activation or connectivity measures, has not been established yet. As a result, crucial evidence for the dynamic functional organisation of the semantic brain network is still missing, since temporal information is essential to disentangle effects that may occur at different stages of semantic processing, e.g., early semantic information retrieval, control processes in decision making, and later imagery or episodic memory processes ( Hauk, 2016 ).…”
Section: Introductionmentioning
confidence: 99%